ENERGY DISPERSIVE X-RAY FLUORESCENCE ANALYSIS (EDXFA) OF TIN CONTENT IN CASSITERITE OBTAINED FROM RAY-FIELD MINING SITE, JOS (FUDMA JOURNAL OF SCIENCES, 2023)
A rapid and precise method was used for the determination of tin in cassiterite from the Rayfield mining site, Jos, using energy dispersive x-ray fluorescence spectrometry, following standard procedures.Theapplication of the technique is very precise when compared to solution methods of analysis.Sampling was conducted by collecting thirty cassiterite samples from ten cassiteriteheaps at the mining site, placed into labeled polyethylene container in triplicates. The samples were dried under laboratory condition for two weeks, ground, sieved and 4g homogenous sample representative was mixed with 1g lithium tetraborate binder and pressed into pellets, dried at 1100C and analyzed. The average percentage of tin in the cassiterite was 19.57%. Other constituents of the cassiterite as analyzed include: Fe(13.70%), Ti(15.90%), Si(23.81%), Zr(8.44%), Al(8.55%),Nb(6.30%), Ta (1.59%), Ca(0.79%), Mn (0.53%), Cr (0.32%), V(0.35%), and Zn(0.15%). Silicon is the predominant element in the cassiterite. Tin is assessed because it is extensively used in many modern high-tech industrial applications, supper-alloys and electronics industry. The EDXRF technique can also provide a rapid evaluation of the economic potential of a geological deposits thereby providing its value both to the miningindustry and to the community impacted by the geological exploitation activities.
Keywords: Cassiterite, Tin,Jos Ray-Field, Energy Dispersive X-ray Fluorescence Analysis, pellet